The Use of Google Meet For Online Microteaching - Dwi Riyanti (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2021)
The social distancing and the closure of schools during the Pandemic force both teachers and students to teach and study remotely. In order to facilitate pre-service teachers learning to teach, the instructor of the Microteaching who is also the researcher opted to use Google Meet (GM) as a teaching platform in Microteaching class. Aiming at uncovering the perspectives of pre-service teachers in using GM as an online teaching platform for teaching their peers, the current study involved the sixth semester students in Microteaching class as its research participants. The main data were obtained through open-ended questionnaire. To triangulate the data, the videos of five pre-service teachers’ teaching demonstrations and five students’ written reflections were also used as a source of data. The obtained data were analyzed thematically based on the emerging themes. In so doing, the researcher firstly read the results of the open-ended questionnaire and the students’ reflection closely and started codifying the data. The findings show that preservice teachers have positive impression toward the use of GM and consider that as useful in the pandemic time. In terms of the challenge they faced, internet connection was found to be the major obstacle in teaching peers using GM.